Enfoque pedagógico y curricular para la primera infancia: convergencias entre los referentes del Ministerio de Educación Nacional y la propuesta de Reggio Emilia (2020)
This work seeks to analyze what pedagogical and curricular principles are relevant for early childhood educational institutions that wish to open in Colombia and want to follow the Reggio Emilia approach To achieve this objective, it was carried out a documentary review of the curricular and pedagogical guidelines proposed by the Ministry of National Education of Colombia in the Política de Estado para el Desarrollo Integral de la Primera Infancia De Cero a siempre, its guiding activities and the guidelines proposed by the Reggio Emilia pedagogy. Subsequently, a dialogue between the Policy, its guiding activities and the Reggio Emilia pedagogy was stablished to identify its curricular and pedagogical principles, with the aim of helping a new kindergarten to incorporate these components.